Mengintegrasikan Strategi Sumber Daya Manusia dan Sociopreneur untuk Mewujudkan Bank Sampah Berdaya di Bekasi - Tiarapuspa Tiarapuspa; Dini Hariyanti; Rakendro Wijayanto; RA Hera Purnami K; Ida Sri Wulandari; Dewa Lima Vadillah; Arlina Intan Regita; Dewi Anggraeni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The Community Service Program (PKM) was conducted to empower waste bank managers in Mangunjaya Village, Bekasi, through the integration of human resource (HR) strategies and the concept of sociopreneurship. The activity took place on January 16, 2025, organized by five PKM teams from Trisakti University, and was attended by 30 waste bank managers. The program was designed using a participatory approach that included team management training, basic financial literacy, branding and digital marketing strategies, and mentoring in the development of recycled products. The implementation methods consisted of lectures, group discussions, hands-on waste sorting practices, and evaluation through a post-test assessment. The results indicated a 35% increase in participants’ understanding, improvement in the quality of recycled products, and expanded marketing reach through online platforms. The implementation of this program provided tangible benefits, including enhanced managerial capacity of waste bank managers, the development of a social entrepreneurship mindset, and the creation of new environmentally based economic opportunities. Furthermore, the program contributed to the development of empowered waste banks with the potential to become drivers of the circular economy in their region.